Sistem Infromasi Pengurusan Pemohonan Balik Nama Sertifikat Hak Milik Tanah - Rafika Al Khairiyah; Yogi Wiranto (Bulletin of Multi-Disciplinary Science and Applied Technology, 2021)
In this day and age, the development of information technology is developing so fast, this can be seen and proven from the use of computers in solving various existing problems, especially those related to computerization. Advances in information technology provide great opportunities for companies or agencies to implement computerization as an information system. In this case, the writer chooses the main discussion in this report is the information system for the management of a land title certificate title request, which is a tool to solve the problem of requesting a reverse land title certificate application. The observation method taken by the author is to take and collect data from the notary office. In addition, the author collects data from books or literature related to the discussion that the author wants to describe and directly conducts questions and answers with the land certificate management section at the notary's office. This aims to facilitate the author in completing reports on information systems in handling requests for a title to land title certificate.